Open Source Software Superstream Series Go-Generics, Modules, and the Future of Open Source Go Programming - Hightower, Kelsey; Griesemer, Robert; Taylor, Ian; Boursiquot, Johnny; Pistunovich, Natalie; Jackson, Nic (O'Reilly Media, Inc., 2021)
Go is now over a decade old, but that doesn't mean it's showing its age. As open source projects across industries have adopted Go, the language has continued to grow and change to meet their needs. Recent and forthcoming additions to the language, such as generics and modules, will alter Go programming dramatically. What do these developments mean for adoption? (Why, for example, is Go the language chosen by so many CNCF projects?) And what features do expert Go developers see as the backbone of the future of programming? Join us to hear expert insight into how the Go language is changing open source development, what makes it right for so many open source projects, and how developers can use Go's unique new features to build secure, reliable, and efficient applications. About the OSCON Superstream Series: Each day in the four-part OSCON Superstream Series covers a different programming language and its ecosystem, with unique sessions including keynotes from language luminaries, debates on controversial topics, and hands-on coding talks. And they're packed with insights from innovators and the latest tools and technologies to help you stay ahead of it all. What you'll learn-and how you can apply it Learn how best to approach using generics in Go code Discover how to extend Go applications Understand techniques for working in someone else's codebase Find out what to do when concurrency goes wrong in your Go applications This Superstream is for you because ... You're a Go developer who wants to learn how newer features such as generics will affect your code and applications. You're a software developer interested in learning more about Go as a language for developing tools, web services, or working with distributed systems. You're an engineer, developer, or DevOps specialist looking to understand how Go is shaping observability and container management. Prerequisites Come with your questions Have a pen and paper handy to capture notes, insights, and inspiration Recommended follow-up: Take Introduction to the Go Programming Language (live online training course with Jay McGavren) Explore Understand Go (expert playlist by Jay McGavren) Read Head First Go (book) Read Concurrency in Go (book) Read Learning Go (early release book) Read Cloud Native Go (early release book) Read The Go Programming Language (book) Play in the interactive Go Sandbox.